Implementasi Pembelajaran Sejarah Berdiferensiasi di SMA Negeri 2 Banjarmasin - Hermawan, Muhammad Dody; Farisi, Akhmat (Lambung Mangkurat University, 2023)
This research is motivated by the on going implementation of the independent curriculum at SMAN 2 Banjarmasin. Oriented to the learning needs of students in various historical lessons shows the need for implementing differentiated learning. The purpose of this research is to describe the implementation of differentiated learning by history teachers at SMAN 2 Banjarmasin. The research method uses a qualitative approach with descriptive methods. Sources of data obtained from observation, interviews and documentation. Primary data collection was carried out on school principals, history teachers and students in class X2 at SMA Negeri 2 Banjarmasin. Meanwhile, secondary data was obtained through a review of documents related to the Merdeka curriculum. The process of data analysis is done by reducing data, presenting and drawing conclusions. The results of the study show that the implementation of differentiated learning by history teachers at SMAN 2 Banjarmasin is carried out independently by referring to the needs of each student based on the initial diagnostic results. the teacher gives the test. In reality, the independent curriculum encourages the growth of innovation and creativity in learning. The teacher has an important role in exploring the interests of students so that they can support the achievement of a meaningful learning through the application of differentiated learning